Displacement Economies in Africa Paradoxes of Crisis and Creativity - Hammar, Amanda (Africa Now, 2014)
Large-scale displacement - whether caused by war, state-related political or development projects, different forms of political violence, structural crisis, or even natural disasters - evokes many stereotyped assumptions about those forcibly displaced or emplaced. At the same time there is a problematic lack of attention paid to the diversity of actors, strategies and practices that reshape the world in the face (and chronic aftermath) of dramatic moments of violent dislocation. In this highly original volume, based on empirical case studies from across sub-Saharan Africa, the authors reveal the paradoxical effects, both intended and unexpected, that displacement produces, and that manifest themselves in displacement economies.